Long-term outcome of adult patients with total anomalous pulmonary venous connection: data from the SACHER registry and a French center. (25th November 2020) - Touray, M; Bouchardy, J; Schwerzmann, M; Greutmann, M; Tobler, D; Engel, R; Harald, G; Pruvot, E; Blanche, C; Sekarski, N; Ladouceur, M; Rutz, T
Abstract: Introduction: Total anomalous pulmonary venous connection is a rare cyanotic congenital heart disease, where all pulmonary veins aberrantly connect to a systemic vein or the right atrium. The only curative treatment is surgery allowing the patients to reach adulthood. This study describes the long-term outcome of these individuals focusing on arrhythmias. Methods: Clinical, surgical, imaging and invasive data were retrospectively reviewed from 7 centers participating in the Swiss Adult Congenital Heart disease Registry (SACHER) and one French center. Results: A total of 57 patients were identified and analyzed 22±8 years after surgery. At last follow-up, 21% of patients presented cardiac symptoms, mainly palpitations. No patient had pulmonary hypertension or a relevant valvulopathy. Echocardiography revealed in 5 (8.8%) patients a dilated right ventricle (RV) and in 3 (5.3%) patients a diminished RV systolic function. Exercise capacity was normal in most patients (table). Cardiac magnetic resonance imaging found in 2 (4%) had a residual shunt with an mean Qp:Qs of 1.25, due to a single anomalously connected pulmonary vein. Holter recordings revealed arrhythmias in 23% of patient. Ten (17.5%) had atrial fibrillation, flutter or tachycardia. Three (5%) patients presented ventricular arrhythmias: two patients showed non-sustained ventricular tachycardia and one patient complex ventricular extrasystoles. Four patients (7%) were on antiarrhythmic medication for supraventricular arrhythmias. Three patients (5%) underwent an electrophysiological study with a mean time since surgery of 20 years. Three (5%) patients underwent pacemaker implantation within 3 weeks to 36 months after surgical correction, which were removed in 2 patients after 7 years. Age and the presence of a valvulopathy at follow-up predicted tachyarrhythmia on binomial logistic regression analysis (p<0.03). Conclusions: In adult survivors after TAPVC repair, supraventricular but also ventricular arrhythmias are frequently observed which appears to be related to age and valvular lesions at follow-up. This study underlies the importance of long-term follow-up as some of the patients currently without arrhythmia will probably develop rhythm disorders in the future. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): Unrestricted grant by Actelion SA, Switzerland